Colonialism, culture, and resistance - Panikkar, K. N. (Oxford University Press, 2007)
"How did resistance to colonialism form a source of alternative modernity in India? Why did the process fail to strike roots? Building upon four decades of serious research, this unique collection discusses different forms of resistance to colonialism and their role in the formation of alternative modernity. It also provides an engaging account of the development of political and cultural consciousness in the subcontinent.